Economic Analysis of Legal Regulations Regarding Liability for Loss Resulting from a Dangerous Product - Kuźmicka-Sulikowska, Joanna (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
The article considers fundamental issues associated with economic analysis of legal regulations pertaining to liability for damage caused by a dangerous product. The discussion is conducted from the perspective of a lawyer analysing the conclusions stemming from economic analyses of the aforementioned liability by individual authors, which constitutes a base for subsequent observations. The relationships between the various potential configurations of manufacturer liability are discussed, in particular a situation where such liability is not stipulated, as well as where there is the introduction of liability based on the risk or fault principles and the ensuing motivation for maintaining an appropriate level of carefulness. Attention is focused on the search for an economically efficient solution. An analysis of current regulation is performed, as well as de lege ferenda conclusions grounded in economic analysis of law with reference to the shape of the regulatory liability regime for damage caused by a dangerous product. Many reservations are also listed, including ones concerning the fact that it does not seem that the legislative process should be guided only by conclusions stemming from economic analysis of law (especially considering the differences of opinion in that area), which does, however, unquestionably constitute a useful tool in such matters.
Keywords: liability for loss; dangeros product; economic analysis; legal regulations